Peran Manajemen Energi terhadap Efisiensi Konsumsi Listrik Rumah Tangga di Indonesia - Dede Mulyana; Ade Nuryana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Household electricity consumption in Indonesia continues to increase along with economic growth, urbanization, and the development of digital technology. This condition contributes to a growing burden on the national energy supply system and increases the potential for carbon emissions. This study aims to analyze the role of energy management in improving household electricity consumption efficiency in Indonesia. The research employed a literature review method with a qualitative approach through content analysis, thematic analysis, and comparative analysis. Data were collected from various reputable academic sources, including Scopus, ScienceDirect, Springer, Emerald, IEEE Xplore, Taylor & Francis, SINTA, and Google Scholar. The reviewed literature was limited to journal articles published between 2021 and 2026 and academic books published between 2016 and 2026. The findings indicate that household electricity consumption efficiency can be enhanced through the implementation of smart technologies, such as smart meters, smart home systems, and energy-efficient appliances, supported by behavioral changes through increased energy literacy and environmental awareness. The main challenges include high initial investment costs, limited public technical knowledge, and insufficient supporting regulations. This study concludes that the integration of technology, continuous education, and government policies can improve household energy efficiency without compromising residents' comfort and can serve as a foundation for developing more effective household energy management programs. Keyword: Energy Management, Energy Efficiency, Households, Energy Consumption.